The relationship between academic self-efficacy and academic performance among CELPAD students - Alzabidi, Talal Saeed Omare (Kulliyyah of Education, International Islamic University Malaysia, 2019)
This study examined the relationship between academic self-efficacy and academic performance of university students in Malaysia. A review of relevant literature identified a gap in the literature concerning the relationship between academic self- efficacy and academic performance. As a result, this study aimed to examine the correlation between academic self-efficacy and academic performance among CELPAD students at International Islamic University Malaysia (IIUM). This study used a quantitative approach which is correlation design. The study sample consisted of 171 CELPAD students at IIUM Gombak. Stratified random sampling was used to collect the data. Study results showed that most of the students had a high level of academic self-efficacy. The results also revealed there was a significant positive moderating relationship between academic self-efficacy and academic performance. However, there were no significant differences in academic self-efficacy based on gender or level of study. Finally, it was found that academic self-efficacy had a significant effect on academic performance. Additionally, the results from this study suggest that future research could reduce the dimensions used to measure academic self-efficacy, and increase, by more than 10 items, those used to measure academic performance. Moreover, further research could also explore the mediation of other variables and involve students' CGPA and passive performance.